ASEAN cooperation to combat transnational crime: progress, perils, and prospects - Sundram, Pushpanathan (Frontiers in Political Science, 2024)
The Association of Southeast Asian Nations (ASEAN) has grappled with the persistent threat of transnational crime (TC) in Southeast Asia since its establishment in 1967. The rising tide of globalisation and technological advancement has only exacerbated the problem, leading to the evolution and organisation of various criminal activities. As ASEAN faces a multitude of non-traditional security challenges that transcend national borders, including climate change, infectious diseases, and resource scarcity, TC remains a critical concern that could jeopardise regional stability and security. This article undertakes an extensive analysis of ASEAN's endeavours to combat TC. It delves into key documents outlining ASEAN's commitment, highlights the significant achievements, and identifies the challenges facing the region. The qualitative study evaluates the effectiveness of ASEAN's response to TC within its cooperative framework and core principles. Through content analysis, it draws insights from ASEAN's official documents, as well as reports from Interpol and the United Nations Office on Drugs and Crime, to understand the regional efforts in countering TC. The research reveals a range of collaborative efforts initiated by ASEAN to tackle TC. By focusing on examples of successful operations, such as Operation Maharlika III against human trafficking and Operation HAECHI-I targeting cybercrime, the study underscores the vital role of cross-border cooperation. However, the analysis highlights the challenges posed by the complex nature of TC and the varying capabilities of ASEAN member states. It underscores the importance of regional cooperation and external partnerships to address the evolving threats of TC effectively. In essence, ASEAN's commitment to combating TC is evident through the adoption of strategic documents, joint operations, and capacity-building initiatives. Nevertheless, the evolving nature of TC and its diverse manifestations pose ongoing challenges. A balanced approach in addressing TC is needed that encompasses not only securitisation but also a criminal justice response.